Assessing Consumer Preferences for Organic Vegetables: A Case Study in the Mekong Delta, Vietnam - Khai, Huynh Viet (Information Management and Business Review, 2015)
An increase in consumer’s demand for environmental and health quality has generated the movement of organic agriculture in terms of high-value products. Understanding consumer preferences is very necessary and important for policy-makers to design appropriate policies promoting and developing organic agriculture. This study employed a dichotomous choice contingent valuation model to analyze consumer’s willingness to pay for organic vegetables in the Mekong Delta, Vietnam. Results indicated that the majority of consumers were interested in organically grown products and willing to pay an average price premium of 59% for organic vegetables. Consumers concerned about health and food safety were more likely to purchase and those who have high household income and education also accepted to buy organic vegetables with higher price than conventional ones.